DEVELOPMENT OF A NEW DESIGN METHODOLOGY FOR LARGE SIZE PRODUCTS BASED ON DSM AND DFMA. (May 2020) - Mora, B.; Retolaza, I.; Campos, M. A.; Remirez, A.; Cabello, M. J.; Martinez, F.
Abstract: A new design methodology for long life and large size (Ll-Ls) products called Design for Installation (DfI) is proposed. Ll-Ls products are usually made up of large parts that need to be assembled on field. The proposed methodology, based on adapted Design Structure Matrix (DSM) and Design for Manufacturing and Assembly (DfMA) methods, enables to optimize the design of a Ll-Ls product in order to reduce time and cost of the installation process. The new methodology works with a conceptual design of the product and the weight and size restrictions given by logistic factors as inputs.